Immune reconstitution inflammatory syndrome, a controversial burden in the East African context: a systematic review and meta-analysis - Geteneh, Alene; Andualem, Henok; Belay, Demeke Mesfin; Kiros, Mulugeta; Biset, Sirak (Frontiers in Medicine, 2023)
It is well established that starting antiretroviral therapy (ART) increases a patient's life expectancy among HIV-positive individuals. With regard to the HIV pandemic, the start of ARTs for the vast majority of HIV-positive people is the main worry, as are any negative effects from immunological restoration. The prevalence of HIV-associated immunological reconstitution inflammatory syndrome (IRIS) is poorly estimated due to Africa's underdeveloped infrastructure, particularly in Eastern Africa. This study thus compiled data regarding the magnitude and associated factors for IRIS in the context of Eastern Africa. Accordingly the development of HIV-associated IRIS in Eastern Africa was estimated to be 18.18 % (95% CI 13.30-23.06) in the current review. The two most common predictors of IRIS associated with Eastern Africa were the lower pre-ART CD4 T-cell count of 50 cells/µl and the low baseline body mass index (BMI) level. Therefore, attention should be focused on the early detection and care of HIV-associated IRIS to reduce the morbidity and death caused by IRIS.